Optimal tax rates in South Africa: new empirical insights to the existing debate. (19th June 2020) - Kavese, Kambale; Phiri, Andrew
The current study contributes to the existing debate on optimal taxes in South Africa by estimating Scully's optimal tax framework using the ARDL framework applied to quarterly data collected between 2002Q1-2017Q4. Notably, our study differs from previous studies in two ways. Firstly, our current study distinguishes between revenue-maximising and growth-maximising optimal tax rates. Secondly, we go beyond the traditional reliance on aggregated tax rates and provided optimal tax estimates for six sub-categories of tax rates employed by South African fiscal authorities (i.e., taxes on income, profit and capital, taxes on property, VAT, general fuel levy, excise duty, and taxes on international trade). Our empirical results indicate that fiscal authorities have generally implemented revenue-maximising tax policy during economic recessions whilst leaning towards growth-maximising tax rates during expansions periods. Based on these findings, the paper manifests policy advice for South African fiscal authorities in their quest for improving the country's economic performance.